THE SIGNIFICANCE OF STATE POLICY REGARDING YOUTH IN DIAGNOSTIC ASSESSMENT OF THE EDUCATION LEVEL OF TEENAGE STUDENTS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
In this article, the importance of the state policy on youth in the diagnostic assessment of the educational level of adolescent students is described, as well as relevant conclusions are drawn on this topic.